A note on a stochastic Holling-II predator–prey model with a prey refuge. Issue 7 (May 2020) - Zou, Xiaoling; Lv, Jingliang; Wu, Yunpei
Abstract: A correction is noted to the previously published paper (Zou and Lv, 2017). Regularity, positive recurrence and stationary distribution are considered in this paper. A complete threshold analysis of strong stochastic persistence and extinction is investigated. Stochastic Hopf bifurcation is considered from the viewpoint of numerical simulations.